Managerial ties, business model innovation & SME performance: Moderating role of environmental turbulence - Makhmoor Bashir; Abdulaziz Alfalih; Sudeepta Pradhan (Journal of Innovation & Knowledge, 2023)
Despite the surge in academic and non-academic literature on business model innovation (BMI) and its implications on firm performance, research on the antecedents of BMI is still evolving. Building on institutional theory, we empirically advance extant knowledge by proving that managerial ties play a significant role in BMI and firm performance. We also propose that BMI mediates the relationship between managerial ties and firm performance. In addition, we argue that the relationship between managerial ties and firm performance is contingent on the degree of environmental turbulence. Our analysis of 280 Saudi-based small and medium-sized firms highlights that managerial ties have a positive impact on firm performance. The mediation tests indicated the significance of BMI in the relationship between managerial ties and firm performance. Results, however, do not confirm the moderating role of environmental turbulence. The study brings into perspective that SME owners and managers need to give more attention to managerial ties to support business model innovation.